Impact Of Newly Isolated Bacillus Megaterium (A1) On Degradation Of Feather Waste - A. ANITHA,; R. ESWARI, (International Journal of Pharma and Bio Sciences, 2012)
Feather keratin is highly resistant to degradation, but some keratinase producing microorganisms can easily degrade these insoluble keratins. These keratinase producing species have an important application in removal of poultry waste and recycled into valuable byproduct. A feather-degrading bacterium with high keratinase activity was isolated and identified as Bacillus megaterium (A1). The selected organism showed keratinase activity of 72.875 IU/mg and the protein content of 4 mg/ml. Maximum enzyme production was observed on 96 hr. The intense feather degrading was achieved in 35°C and initial pH adjusted to 7.5. Among the extra nitrogen or carbon sources used, significant improvement in yield of keratinase was obtained when grown in medium containing 2% feather meal. The protein profile was analyzed in SDS-PAGE showed multiple bands. Zymography analysis showed a single band with molecular weight of 46 KDa which corresponds to keratinase activity. Immobilized cells of B. megaterium (A1) had highest durability to degrade feather keratin. Fourier Transform Infrared Spectroscopy (FTIR) showed that the change in the functional group was catalyzed by the unique enzymes of B. megaterium (A1). From this study, Bacillus megaterium isolated from feather dumped soil can be used as a potential candidate for degradation of feather and for can be used as additives in poultry field.